Lactiplantibacillus plantarum ZP-6 mitigates polystyrene nanoplastics-induced liver damage in colitis mice via the gut-liver axis - Zhao, Lili; Wei, Zihan; Wang, Yibin; Chen, Wanrong; Zhang, Wenjing; Xie, Mengfei; Chen, Hong; Zhang, Yiping; Gao, Haiyan; Jiang, Xiaobing (Frontiers in Microbiology, 2025)
IntroductionNanoplastics (NPs) have become a ubiquitous environmental pollutant that exhibits a tendency to accumulate in large quantities in the tissues of the host body (enteritis patients) with intestinal damage and poses a serious health risk, for which there is currently no suitable method for in vivo clearance. Studies have found that lactic acid bacteria has the potential to eliminate pollutants from the body.MethodsIn this study, we investigated the capacity of Lactiplantibacillus plantarum ZP-6, a strain isolated from human feces with demonstrated in vitro microplastic-binding activity, to alleviate the physiological toxicity of polystyrene nanoplastics (PS-NPs) in healthy and colitic murine models. Then, we investigated the capacity of Lactiplantibacillus plantarum ZP-6 to alleviate the physiological toxicity of polystyrene nanoplastics (PS-NPs) in healthy and colitic murine models.ResultsOur findings revealed that PS-NPs exposure resulted in systemic accumulation, triggering organ pathology and inflammatory responses in the liver and colon. Dietary intervention with Lactiplantibacillus plantarum ZP-6 significantly reduced PS-NPs retention in blood and tissues while enhancing fecal excretion, restoring hepatic, renal, and colonic histopathology to baseline levels. Mechanistically, ZP-6 downregulated pro-inflammatory cytokines (IL-1β, IL-6, TNF-α) and anti-inflammatory IL-10 in affected tissues. Gut colonization dynamics demonstrated transient enrichment of ZP-6, which facilitated PS-NPs adsorption and fecal clearance. Concurrently, ZP-6 upregulated mucin gene Muc2 and tight junction components (OCLN, CLDN1), reinforcing the intestinal epithelial barrier and impeding PS-NPs translocation. Metabolomic analysis further indicated that ZP-6 rectified PS-NPs-induced hepatic metabolic dysregulation via the gut-liver axis.ConclusionThese results elucidate a multifaceted probiotic mechanism for NPs detoxification, providing a promising translational strategy to counteract nanoplastic-related health hazards.